Optimal fiscal policy with heterogeneous agents - Marco Bassetto (Quantitative Economics, 2014)
The aim of this paper is to study the relationship between the intertemporal behavior of taxes and wealth distribution. The optimal-taxation literature has often concentrated on representative-agent models, in which it is optimal to smooth distortionary taxes. When tax liabilities are unevenly spread in the population, deviations from tax smoothing lead to interest rate changes that redistribute wealth. When a “bad shock” hits the economy, the optimal policy will then call for smaller or larger deficits, depending on the political power of different groups. This effect is particularly relevant in the case of large shocks to government finances, such as wars.
Keywords: 330; Optimal taxation; heterogeneous agents; asset prices; distortion; net trade